Negotiating business narratives : fables of the information technology, automobile manufacturing, and financial trading industries /: fables of the information technology, automobile manufacturing, and financial trading industries. ([2018]) - Borins, Sandford F, 1949-; Herst, Beth F, 1962-
No abstract available